Quantitative determination of solid electrolyte interphase and cathode electrolyte interphase homogeneity in multi-layer lithium ion cells. (1st December 2021) - Heidrich, Bastian; Börner, Markus; Winter, Martin; Niehoff, Philip
Highlights: SEI and CEI composition varies even on single electrode sheet. Notable variation of SEI in 5 cm² area and of CEI at edge and outer sheet. Washing: improved homogeneity, but removal of organic SEI. SD of organic SEI thickness correlates with SD of SEI composition. Multiple measurements required for reliable statements on surface layer composition. Abstract: This X-ray photoelectron spectroscopy study of three multi-layer lithium ion cells is based on a total of 106 measurements. A formula is derived utilizing the mean relative standard deviation (mean rel. SD) of the surface composition to illustrate the solid electrolyte interphase (SEI) and cathode electrolyte interphase (CEI) homogeneity within certain areas. Within an area of 1 cm², the mean rel. SD is 8% and 9% for negative and positive electrodes. Within an area of 5 cm², these values increase to 24% and 14%, indicating reduced homogeneity especially for negative electrodes. Negative electrode samples from the electrode sheet edge and outer sheet have no different homogeneity. Positive electrode samples, instead, have different composition at these positions. Sample washing increases homogeneity but also removed organic SEI components. Homogeneity between different cells is as similar as within one cell. Varying thicknesses of the organic SEI layer are identified as main factor for reduced SEI homogeneity (mean rel. SD 45%). The inorganic SEI has comparable thickness even between different cells (mean rel. SD 7%). This might indicate the importance of the inorganic layer for cell performance. The calculated CEI thicknesses are ∼0 nm, indicating only scattered surface reactions and no real passivation layer. Graphical abstract: Image, graphical abstract